PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA LPD KESIMAN DI DENPASAR - Arthawan, Kadek Juli; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
Research was conducted on employees LPD Kesiman. The purpose of this study was to determine the effect of transformational leadership style and job satisfaction in LPD Kesiman, Denpasar. The population in this study were employees of LPD Kesiman totaling 38 employees called saturated sampling technique. The analysis tool used is multiple linear regression techniques. The analysis showed that transformational leadership style berpengruh positive and significant impact on employee performance, it shows that the higher the level of perceived transformational leadership style employees, the greater the perceived performance of employees. For job satisfaction variables posotif and significant influence on employee performance, this shows that the higher the level of perceived employee job satisfaction, the greater the perceived performance level of employees. LPD Kesiman parties should always consider the level of transformational leadership style and job satisfaction felt by employees. It aims to improve the performance of employees at LPD Kesiman, Denpasar.
Keywords: transformational leadership, job satisfaction, job performance